2018
DOI: 10.1002/pits.22154
|View full text |Cite
|
Sign up to set email alerts
|

School reentry services for students with chronic health conditions: An examination of regional practices

Abstract: Students experiencing chronic health difficulties represent a growing population in public schools. Given the unique challenges faced by these students including increased absences, resulting academic, and social/emotional/behavioral deficits, it is vital that schools are prepared to adequately meet their needs. One of the sometimes daunting tasks faced by these students and their families is the school reentry process, which occurs when the child returns to school following an extended period of time away. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Many children with cancer are living, surviving and studying in different environments (Boles et al, 2017;Schilling & Getch, 2018). During cancer treatment, children usually receive educational support in alternative settings such as home or hospital (Boles & Winsor, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many children with cancer are living, surviving and studying in different environments (Boles et al, 2017;Schilling & Getch, 2018). During cancer treatment, children usually receive educational support in alternative settings such as home or hospital (Boles & Winsor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for children with cancer, one of the greatest educational and social challenges are returning to school after multiple or prolonged absences (Boles et al, 2017;Chen et al, 2015;Choquette et al, 2016). According to Schilling and Getch (2018), 'school re-entry refers to the return to school and reintegration into the school setting following diagnosis, prolonged hospitalization, and/or general time away from school' (p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers may need to develop lessons in advance if a child needs to be hospitalized for an extended period of time, and in some cases, homebound education might be necessary. Educational and health plans may include accommodations for modified or alternative physical education and should discuss how the educational team will address extended absences due to medical complications (Schilling & Getch, 2018).…”
Section: Psychoeducational Implications and School-based Intervention...mentioning
confidence: 99%
“…Research also suggests that school personnel are often unprepared to address the needs of children with chronic health conditions. Schilling and Getch (2018) reported that only 44% of surveyed special education directors received formal training in meeting the needs of students with chronic health conditions, and they argued that more in-service training in this area is necessary. These trainings may be necessary for schools with students diagnosed with Marfan syndrome.…”
Section: Social-emotional and Behavioralmentioning
confidence: 99%
“…Likewise, Tsimicalis et al (2018) documented the compounding academic and social adversities faced by students returning to school after long-term cancer treatment. Although careful planning for school reentry is key to mitigating the effects of extended medical absences (DuPaul et al, 2018), scholars such as Schilling and Getch (2018) found that schools are often underprepared to create or implement plans to accommodate such periods of schooling interruption.…”
Section: Part 1: Who Are Sife Students?2mentioning
confidence: 99%